Pediatric injuries: The etiology and associated factors as seen at a Mission Hospital in Aba, Southeast Nigeria - Onyarugha, Chukwuemeka Ngozi; Okoronkwo, Nneka Chioma; Ohanenye, Chioma Akunnaya (Indian Journal of Child Health, 2019)
Background: Pediatric injuries constitute a significant health burden, particularly in developing countries, including Nigeria. Comprehensive and case-specific management including a good database is largely unavailable in these countries. Aim: This study aims to determine the causes and associated factors of pediatric injury (PI) in Aba, Southeast Nigeria. Materials and Methods: This was a retrospective study conducted for a period of 3 years (January 1, 2015–December 31, 2017) in a Mission Hospital in Aba. Data were obtained from the case notes of children aged 16 years and below, who were seen for injuries at the accident and emergency department (AED). Information extracted from the case files included the sex, age, nature of injury, venue of injury, body areas involved, and outcome of treatment. Results: PI constituted 13% of all trauma cases seen in the AED during the study period. There were 54 males and 39 females, giving a male:female ratio of 1.4:1. The leading mechanisms of injury were road traffic accident (RTA), 36 (38.7%) and domestic accidents, 27 (29%), while gunshot wounds 3 (3.3%) constitute the least. RTA occurred most frequently in the age groups of 6–15 years, 24 (25.8%). Again, 91.7% of RTA occurred in the urban area and involved mostly pedestrians crossing the road (55.6%). Children aged 0–5 years, 34 (36.6%) were the most frequently involved in PI. Leading mechanisms of injury in this age group were domestic accidents, falls, and burns. There was a statistically significant association between age and mechanism of injury (p=0.000). Mortality rate was 2%. Conclusion: Pediatric injuries constituted 13% of all trauma cases in this study. Children aged 0–5 years were the most frequently involved in PI. RTA and domestic accidents were the leading causes of PI. Very young children at home and older children crossing the road were vulnerable to pediatric injuries.